Partnership based on Triple Helix for Tourism and Peace for Sustained Development Bromo Mountain - Karisma Sri Rahayu; Titing Kartika; Rahmat Yuliawan; April Kim Lalisan; Rashid Ating; Sovia Rosalin (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the implementation of the Triple Helix model, which facilitates collaboration among academia, industry, and government, in advancing sustainable tourism and promoting peace at Mount Bromo, Indonesia. The swift expansion of tourism in this region has generated economic advantages while underscoring the necessity for strategic, sustainable governance to reconcile development with environmental and social equilibrium. The study investigates governance challenges and the roles of various stakeholders in tourism development, highlighting the necessity for integrated management practices to enhance local community engagement, innovation, and economic advancement. This study employs descriptive qualitative methods to achieve three primary objectives: enhancing partnerships for tourism governance, creating tourism clusters, and promoting innovation in tourism management. Research indicates that although the Triple Helix model effectively aligns stakeholder initiatives, enhanced integration, especially in education and community involvement, is necessary to realize the model's potential fully. This research enhances the tourism governance literature by illustrating how the Triple Helix model can facilitate sustainable tourism, stimulate economic development, and cultivate peaceful, inclusive societies.